2017
DOI: 10.1386/qsmpc.2.1.29_1
|View full text |Cite
|
Sign up to set email alerts
|

The contextual integrity of the closet: Privacy, data mining and outing Facebook’s algorithmic logics

Abstract: In the 2010 book The Facebook Effect by David Kirkpatrick, Facebook founder Mark Zuckerberg made the claim that ‘users have one identity’. Through a critical theoretical analysis of a series of case studies of people being outed by Facebook, this article argues that ‘one identity’ and Facebook’s use of algorithms to drive profits are fundamentally incongruous with prevailing intersectional scholarship. The case studies articulate a theoretical framework that ties intersectional conceptions of gender and sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…A scholarship on the implications that platform algorithms -and platform affordances more generally -raise for LGBTQ+ users has emerged over the past few years. For example, researchers have suggested that the predictive nature of platform algorithms can result in outing LGBTQ+ people online by promoting default settings like publicness and visibility (Cho, 2018;Werbin et al, 2017). Some scholars have illustrated how digital platforms, guided by industry imperatives, rely on binary classification systems that reproduce cisheteronormative assumptions about gender and sexual orientation (Bivens & Haimson, 2016;Lingel & Golub, 2015) that can further lead to online harassment against LGBTQ+ users (Albury et al, 2020;Blackwell et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A scholarship on the implications that platform algorithms -and platform affordances more generally -raise for LGBTQ+ users has emerged over the past few years. For example, researchers have suggested that the predictive nature of platform algorithms can result in outing LGBTQ+ people online by promoting default settings like publicness and visibility (Cho, 2018;Werbin et al, 2017). Some scholars have illustrated how digital platforms, guided by industry imperatives, rely on binary classification systems that reproduce cisheteronormative assumptions about gender and sexual orientation (Bivens & Haimson, 2016;Lingel & Golub, 2015) that can further lead to online harassment against LGBTQ+ users (Albury et al, 2020;Blackwell et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This shift from active military engagement abroad during the early years of the War on Terror to a strategy largely characterized by intelligence gathering, drone warfare, and mass surveillance, places The Flash within a fundamentally transformed culture strongly influenced by modern security politics and consequently also influenced by suspicion about both corporate and government surveillance. In particular, many scholars argue that despite social and legal progress, LGBTQ populations remain disproportionately vulnerable to regimes of mass surveillance and big data, as, for example, hidden exchanges of data revealing sexual preference may become the basis of automated discrimination, or nongender-conforming bodies can be marked as a threat by airport security (Bhattasali and Maiti, 2015;Conrad, 2009aConrad, , 2009bLewis, 2010;Phillips and Cunningham, 2007;Werbin et al, 2017). As a result, metaphors about closeting and secrecy in The Flash are differently inflected in relation to, on the one hand, modern gains made by the LGBTQ rights movement, and, on the other hand, increasing fears associated with pervasive state and corporate surveillance, as well as transformations in security politics.…”
Section: Introductionmentioning
confidence: 99%